Determinants of audit quality: competence, independence, professional skepticism, and time budget pressure - Octaviani, Ananta Pasya; Sudarmanto, Eko; Hidayat, Imam (Universitas Muhammadiyah Malang, 2026)
Purpose: This study aims to examine the effect of auditor competence, independence, professional skepticism, and time budget pressure on audit quality at Public Accounting Firms (PAFs) in the Tangerang Raya region. Methodology/approach: This study employs a quantitative research approach using primary data collected through questionnaires distributed to auditors working at Public Accounting Firms in Tangerang Raya. The sampling technique used is purposive sampling. The collected data were analyzed using multiple linear regression analysis. Findings: The results indicate that competence, independence, and professional skepticism have a positive and significant effect on audit quality. However, time budget pressure does not have a significant effect on audit quality, suggesting that auditors are able to maintain audit quality despite experiencing time constraints. Practical and Theoritical contribution/Originality: This study contributes theoretically by strengthening the application of attribution theory in explaining internal and external factors that influence audit quality. Research Limitation: This study is limited to auditors working at Public Accounting Firms in the Tangerang Raya region and only examines four independent variables, which may limit the generalizability of the results.